The Role of Nahdlatul Ulama in Local Political Dynamics in North Sumatra in 2024 - Muhammad Rifai; Windawati Pinem (UIN Mataram, 2026)
This study aims to examine the role of Nahdlatul Ulama in local political dynamics in North Sumatra in 2024. NU as the largest Islamic organization in Indonesia has a significant influence on the social, cultural, and political life of the community. However, in practice, the involvement of religious organizations in the political sphere often faces the risk of politicization that can affect the independence of the organization. Therefore, this research is directed to understand the form of NU's role in local politics and the factors that influence this involvement. This study uses a descriptive qualitative research method with data collection techniques through in-depth interviews, direct observation, and documentation. The informants in this study are the Deputy Chairman of the Nahdlatul Ulama Regional Management (PWNU), the Deputy Secretary of the Nahdlatul Ulama Regional Management (PWNU), and the Katib of the Nahdlatul Ulama Regional Management (PWNU). The results of this study show that Nahdlatul Ulama (NU) in local political dynamics plays a role that emphasizes moral, social, and educational functions rather than involvement in practical politics. The pattern of participation is influenced by social and religious factors that make NU play a role as the moral force of civil society in maintaining the harmony and quality of local democracy, which is carried out through the strategy of organizational neutrality and political education to the community.